Magnesium in Ketamine Administration in Treatment-Resistant Depression - Natalia Górska; Wiesław Jerzy Cubała; Jakub Słupski; Mariusz Stanisław Wiglusz; Maria Gałuszko-Węgielnik; Mateusz Kawka; Agata Grzegorzewska (MDPI AG, 2021)
Relationship between depression and magnesium levels is reported. This observational study examined whether serum magnesium concentration change over time of ketamine treatment course, also whether association between magnesium concentrations and treatment response measured with Montgomery-Åsberg Depression Rating Scale (MADRS) score occurs. Moreover, interlink between changes in Young Mania Rating Scale (YMRS) score, somatic comorbidities, and magnesium concentration was studied. Inpatients with major depressive disorder or bipolar disorder were rated weekly by clinician using MADRS and YMRS. Magnesium levels assessments were carried out weekly, before start of ketamine treatment and then every second infusion and one week after last ketamine infusion. The concentration of Mg2+ ions differs depending on the measurement. The Mg2+ concentration in pre-measurement was significantly higher than in measurement after five infusions (p = 0.031) and after seven infusions (p = 0.003). No significant correlation was observed between changes in magnesium serum levels and MADRS or YMRS. The concentration of Mg2+ ion in course of the treatment was not associated with somatic comorbidities. The study supports data for role of magnesium in treatment-resistant depression, particularly related to ketamine treatment, but provides no clear evidence of straightforward association between magnesium serum concentration and treatment response or comorbidity.